Student entrepreneurial skills in facing ASEAN Economic Community: A case study at Universitas Terbuka, Indonesia - Iqbal Miftakhul Mujtahid; Mery Berlian; Rian Vebrianto; Musa Thahir (International Journal of Evaluation and Research in Education (IJERE), 2023)
As part of the skills demographic bonus towards ASEAN Economic Community (AEC), student preparation still needs to be improved, especially in entrepreneurship skills. The purpose of this research is to find out the entrepreneurial abilities of Universitas Terbuka students and how to improve these abilities. This research was conducted through a mixed methods design consisting of two survey research designs that aim to clearly map and make recommendations from students regarding entrepreneurial skills. This research involved 730 students at the Universitas Terbuka, Indonesia. Data were collected through observation, questionnaires, interviews, and documentation which were then analyzed descriptively and inferentially. The results of the study showed that: i) Students’ entrepreneurial abilities are categorized as good; and ii) Gender affects students’ entrepreneurial abilities. Therefore, it needs support and concrete steps from stakeholders in welcoming the AEC. There are several necessary steps carried out by faculty leaders and the chancellor so that students have the desire to develop an entrepreneurial spirit, including: by conducting regular monitoring and evaluation of Universitas Terbuka students, providing reward and punishment and equal justice without discrimination and providing training in accordance with their fields, giving permission to continue studies and provide training that can support good performance by coordinating and evaluating work.